How Managers' Shared Mental Models of Business–Customer Interactions Create Different Sensemaking of Social Media. Issue 1 (August 2015) - Rydén, Pernille; Ringberg, Torsten; Wilke, Ricky
Building on empirical research, we identify four mental models of business–customer interactions and show how each uniquely affects how managers conceptualize and use social media. The four models are "business-to-customers, " "business-from-customers, " "business-with-customers, " and "business-for-customers." The mental model approach helps explain why managers' use of social media does not necessarily lead to radical changes in their interaction with customers, despite the opportunities facilitated by these media. We provide a conceptual framework that enables managers to introspectively investigate their own mental models and thereby revise their sensemaking and use of social media.